Membrane Bioreactor For Leachate Treatment - Abu Bakar, Noor Fitrah; Ujang, Zaini (2004)
Solid waste that is improperly handled will be a source of pollution to land, air, surface water and groundwater besides creating an odor problem. In this study, a membrane bioreactor (MBR) was utilized as a treatment system for a synthetic leachate that used a microfiltration hollow fibre membrane. The performance of the MBR and the membrane itself were monitored which mainly focused on organic matters and heavy metal removal for lead (Pb), cadmium (Cd), copper (Cu) and zinc (Zn) in the synthetic leachate. The MBR was operated at different backwash interval time i.e. 15, 30 and 60 minutes. This experiment found that the COD removal efficiency was up to 98%. The average heavy metals removal was 94%, 92%, 42% and 75 % for Pb, Cd, Cu and Zn respectively.